Central vein stenosis in a dialysis patient: a case report - Göttmann, Uwe; Sadick, Maliha; Kleinhuber, Kathrin Marie; Benck, Urs Tobias; Huck, Kurt; Krämer, Bernhard; Birck, Rainer (Journal of medical case reports, 2012)
Central vein stenosis is not a rare problem in patients on dialysis. Placement of a central vein catheter for dialysis access substantially increases the risk of central vein stenosis. However, even in patients without a previous history of central vein catheter placement, a stenosis can be found in up to 40% of patients.
Gesehen am 16.04.2018